Breaking vicious cycles of hydrological disasters and socioeconomic inequalities - Giuliano Di Baldassarre; Mariana Madruga de Brito; Sara Lindersson; Frederike Albrecht; Maria Rusca (Hydrological Sciences Journal, 2026)

Co-creating water knowledge: a community perspective - Giulio Castelli; Ben C. Howard; Tanveer M. Adyel; Amir AghaKouchak; Afnan Agramont; Hafzullah Aksoy; Rossella Alba; Pedro H.L. Alencar; Amobichukwu C. Amanambu; Hasnat Aslam; Luna Bharati; Liduin Bos-Burgering; et al. (Hydrological Sciences Journal, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Go together, to go further! Reply to “Human–water research: discussion of ‘Guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants’” - Britta Höllermann; Sally Rangecroft; Melanie Rohse; Eddie W. Banks; Rosie Day; Giuliano Di Baldassarre; Theresa Frommen; Yasunori Hayashi; Karen Lebek; Elena Mondino; Maria Rusca; Marthe Wens; et al. (Hydrological Sciences Journal, 2022)

Bridging the gap: reply to discussion of “Guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants” - Sally Rangecroft; Melanie Rohse; Eddie W. Banks; Rosie Day; Giuliano Di Baldassarre; Theresa Frommen; Yasunori Hayashi; Britta Höllermann; Karen Lebek; Elena Mondino; Maria Rusca; Marthe Wens; et al. (Hydrological Sciences Journal, 2022)

The legacy of large dams in the United States - Giuliano Di Baldassarre; Maurizio Mazzoleni; Maria Rusca (Ambio, 2021)
The sustainability of large dams has been questioned on several grounds. One aspect that has been less explored is that the development of dams and reservoirs often enables agricultural expansion and urban growth, which in turn increase water consumption. As such, dam development influences, while being influenced by, the spatial and temporal distribution of both supply and demand of water resources. In this paper, we explore the interplay between large dams, patterns of population growth and agricultural expansion in the United States over the past two centuries. Based on a large-scale analysis of spatial and temporal trends, we identify three distinct phases, in which different processes dominated the interplay. Then, we focus on agricultural water use in the Southwest region (Arizona, California and Nevada) and explore chicken-and-egg dynamics where water supply partly meets and partly fuels water demand. Lastly, we show that the legacy of dams in the United States consists of a lock-in condition characterized by high levels of water consumption, especially in the Southwest, which leads to severe water crises and groundwater overexploitation when droughts occur.

Guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants - Sally Rangecroft; Melanie Rohse; Eddie W. Banks; Rosie Day; Giuliano Di Baldassarre; Theresa Frommen; Yasunori Hayashi; Britta Höllermann; Karen Lebek; Elena Mondino; Maria Rusca; Marthe Wens; et al. (Hydrological Sciences Journal, 2021)